Effect of Carbon-Neutral Fuel Fed Solid Oxide Fuel Cell System on CO2 Emission Reduction. (30th May 2017) - Tachikawa, Yuya; Matsuzaki, Yoshio; Kawabata, Yasuharu; Sugahara, Mariko; Somekawa, Takaaki; Taniguchi, Shunsuke; Sasaki, Kazunari
Abstract : Carbon-neutral fuel fed solid oxide fuel cell (SOFC) system can achieve highly efficient power generation without any greenhouse gas emissions. In this paper, the influence of supplied fuel species on the SOFC performance has been evaluated by heat and mass balance analysis. The electrical efficiency of carbon-neutral fuel fed SOFCs is quantified and compared with that of conventional fuel fed SOFCs. Then, the effect of electrical efficiency increase on CO2 emission is also investigated. Furthermore, the effect of proton-conducting ceramic materials application as an electrolyte is also discussed to evaluate the influence on the electrical efficiency. The carbon-neutral fuel fed protonic ceramic fuel cells (PCFCs) had an advantage to enhance the electrical efficiency compared with the same fuels fed typical SOFCs. Due to the increase in electrical efficiency, the reduction in CO2 emission was clearly appeared as CO2 emission factor.